2006
DOI: 10.1271/bbb.70.999
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat Treatment on the Antioxidative and Antigenotoxic Activity of Extracts from Persimmon (Diospyros kakiL.) Peel

Abstract: Heat treatment of persimmon peel (PP) increased the antioxidative activity of the 70% ethanolic extract (EE) and water extract (WE) from PP. EE and WE both prevented H2O2-induced DNA damage to human peripheral lymphocytes. The antioxidative and antigenotoxic activities of the PP extracts were significantly affected by heating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 17 publications
2
31
1
Order By: Relevance
“…An interesting aspect is the increased level of lycopene in samples from different regions. Lycopene content increases from north to south reinforcing results published by Kim et al (2006) and Takahashi et al (2006) showing increases in carotenoids and polyphenols concentrations in fruit skins compared to those found in pulps. The same authors had concluded that lycopene concentrations were related with different growing regions, particularly to those with higher sun exposure.…”
Section: <Table 3>supporting
confidence: 81%
See 3 more Smart Citations
“…An interesting aspect is the increased level of lycopene in samples from different regions. Lycopene content increases from north to south reinforcing results published by Kim et al (2006) and Takahashi et al (2006) showing increases in carotenoids and polyphenols concentrations in fruit skins compared to those found in pulps. The same authors had concluded that lycopene concentrations were related with different growing regions, particularly to those with higher sun exposure.…”
Section: <Table 3>supporting
confidence: 81%
“…The protective action of fruits has been attributed to the presence of antioxidants, especially antioxidants vitamins, including ascorbic acid, β-carotene (Giraldi, et al, 2003;Céspedes, et al, 2008;Chen, et al, 2008). Besides carotenoids, Diospyros kaki fruits contain a variety of natural antioxidants (Davies & Hobson, 1981;Clinton, 1998;Davey, et al, 2000;Kim, et al, 2006). Antioxidants are compounds that can delay oxidation of lipids or other molecules by inhibiting the beginning or propagation of oxidative chain reactions (Velioglu, et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[22][23][24][25][26] Explanations for the increase in antioxidant values have been attributed to the release of bound phenolic compounds by the breakdown of cellular constituents and to the formation of new compounds with enhanced antioxidant properties. [27,28] …”
Section: Data On Phenolic Content and Antioxidant Activity Are Means mentioning
confidence: 99%